Fatores capazes de influenciar o apoio dos residentes ao desenvolvimento do turismo religioso em Santa Cruz - RN - Silva, Gilmara Barros da (2014)
This study is about the primary stakeholder management - the resident community, given its participation and support for the development of tourism in touristic destinations. It has as a general aim to analyze the factors that are capable to influence the residents‟ support to the development of religious tourism in Santa Cruz, RN, and the existing interrelationships between factors. In order to achieve this objective, it was necessary to use exploratory and descriptive research, followed by a quantitative approach through questionnaires with 422 residents of Santa Cruz -RN. The study was based on the variables relationship model proposed by Nunkoo and Ramkissoon (2012), it was also used the technique of Structural Equation Modeling - SEM, aiming to explain the relationships between the constructs studied. The results found on the survey suggest that the more residents realize the benefits generated by tourism, as well as trust in government actors in charge of tourism development, the more there will be a propensity to support the development of religious tourism. This result is similar to the one found in the study of Nunkoo and Ramkissoon (2012). We conclude that the structural model that best represents the reality of Santa Cruz -RN is composed of the factors: benefits, costs, and confidence in governmental actors, which are able to influence the support of Santa Cruz‟s residents for the development of religious tourism. It is also noteworthy that it was found a highly significant connection between the factors benefits perceived from tourism and confidence in governmental actors and between both of them, the political support for tourism